Alley farming - Kang, B.T.; Reynolds, L.; Atta-Krah, A.N. (Academic Press, 1990)
Discusses the Development of alley cropping and alley farming, uses of trees and shrubs in fallow systems, hedgegrow establishment and management and benefits for crop production and livestock. Examines the economic aspects and social acceptability of alley farming.